The Effect Of Perceived Value And Customer Satisfaction On Customer Loyalty (Case Study On Solaria Bencoolen Mall Customers) - Wahyuni, Intan Tri; Subandrio, Subandrio (Jurnal Fokus Manajemen, 2024)
The title of this research is the effect of perceived value and customer satisfaction on customer loyalty (case study on Solaria Bencoolen Mall customers). This research is based on the importance of customer loyalty for business companies. Some of the factors that influence customer loyalty are perceived value and customer satisfaction. This study aims to determine the effect of perceived value and customer satisfaction on customer loyalty of customers Solaria Bencoolen Mall restaurant.This type of research is quantitative research with a descriptive approach. The research population is all Solaria Bencoolen Mall restaurant customers. The sample size was 88 people, taken using accidental sampling technique. Data collection using a questionnaire. Data analysis techniques using Multiple Linear Regression analysis. Partial test results show that perceived value has a positive and significant effect on customer loyalty variables (tcount = 3.516 and Sig = 0.001) and customer satisfaction variables have a positive and significant effect on customer loyalty variables (tcount = 5.328 and Sig = 0.000). The simultaneous test results show that the perceived value variable and the customer satisfaction variable together have a significant effect on customer loyalty (Fhitung = 72,988 and Sig = 0.000). The regression equation of the test results is: Y = 4.664 + 0.298 X1 + 0.510 X2, with a Coefficient of Determination value of 63.2% (R Square = 0.632). Where the Coefficient of Determination means that together perceived value and customer satisfaction contribute 63.2% in influencing customer loyalty of Solaria Bencoolen Mall restaurant customers.